Effect of sodium bicarbonate on performance and markers of kidney and gastrointestinal injury during repeated sprints in the heat - Jonathan W. Specht; Marissa Ramirez; Jennifer Raef; Mackenzie Schwartz; Alyssa R. Bailly; Oscar Chavez; Ozan Kumbasar; Jade X. Dawson; Jessica Apodaca; Raul Freire; Whitley C. Atkins; Flávio de Castro Magalhães; et al. (European Journal of Applied Physiology, 2026)
Purpose We tested the hypotheses that sodium bicarbonate (SB) supplementation improves performance, reduces markers of acute kidney injury (AKI) risk, and increases markers of acute gastrointestinal injury (AGI) during repeated sprints in the heat. Methods Using a double-blind design, 10 recreationally endurance-trained participants ingested 0.2 g/kg of body weight of SB or placebo before cycling in the heat (dry-bulb: 40 °C, relative humidity: 20%). Exercise bouts included a 22-min warm-up, then 4-sets of 5 × 6-sec maximal-effort standing cycling sprints. Core temperature (Tc) was measured at baseline, end of warm-up, after set two of sprints, and post-exercise bouts. Urine and plasma collected pre-ingestion and pre-, post-, and 1-h post-exercise were analyzed for markers of AKI risk, AGI, and endotoxemia. Results SB increased peak (average difference between conditions: 21 ± 11 W, condition effect: p = 0.02) and average ( p = 0.03) power across the sprints. Tc increased from pre- to post-exercise (placebo: Δ1.3 ± 0.3 °C, SB: Δ1.4 ± 0.4 °C, time effect: p < 0.001), but there were no effects of condition or interaction. Exercise increased the primary marker of AKI (urinary IGFBP7×TIMP-2, time effect: p = 0.005) but not urinary NGAL. There were no condition or interaction effects for either AKI marker. Plasma I-FABP, a marker of AGI, increased post-exercise bouts (placebo: Δ291 ± 550 pg/mL, SB: Δ397 ± 482 pg/mL, p = 0.03), with no condition or interaction effects. There were no significant effects for markers of endotoxemia (LBP, sCD14). Conclusions SB supplementation improves repeat sprint performance in the heat without altering Tc, markers of AKI risk, or markers of AGI.